Unconventional optical properties of 2D Janus SMoSe induced by structural asymmetry. (1st July 2022) - Zhang, Jing; Wen, Xiewen; Zhai, Tianshu; Wiederrecht, Gary P; Lou, Jun
Abstract: The Janus SMoSe monolayer that is best-known for its structural asymmetry is found to exhibit unconventional optical properties compared with its counterpart MoSe2 . Optical transmittance measurements on monolayers that are directly synthesized on sapphire substrates reveal that the transmittance, as well as the real and imaginary parts of the optical dielectric constants of Janus SMoSe obtained from the Kramers–Kronig constrained analysis, show strong dependence on the polarization direction of the incident light. Meanwhile, the transmittance of the unpolarized light of Janus SMoSe becomes insensitive to light at incident angles up to 30°. The intrinsic dipoles induced by the structural asymmetry of Janus SMoSe are believed to produce these distinct optical properties. By estimating the optical absorption of the intrinsic dipoles and tracing their dependence on the light incident angles, we speculate that the dipoles are not perpendicularly aligned to the in-plane direction of the monolayer, but rather tilted by a small angle between 0° and 10°.